Trend analysis of first year student experience in university - Lekena, L.L.; Bayaga, A. (South African Journal of Higher Education, 2018)
Using the theoretical framework of Tinto (2013), the first objective of the current research was to establish the experience of first year students within the first few weeks of their studies in university, and the second objective addressed some of the problems they faced within those first few weeks. Based on the research objectives, a questionnaire was used as the data collection tool. The total number of participants in the survey was 4 020. This represented 27% (4020 out of 15 217) of all University of the Mega Don (pseudonym) first year students registered in 2014. With regards to disability, the survey results indicate that 34 (0.9%) of the surveyed students have disabilities. However, the majority (327 out of 338 (96.7%)) of these students are not registered with the disability office. More than half of students, especially those from low-income or disadvantaged backgrounds, dropout because they are unable to bear the direct and indirect costs of university attendance or are unable to continue attending when financial needs change. The results indicated that 1 001 (25.7%) of the surveyed students did not attend orientation due to late registration and other reasons. However, 1 604 (48.5%) of the surveyed students would like some orientation type activities to be repeated later in the year. The findings of this study show that 1 835 (47.3%) of the students did not know where the Student Development Support (SDS) was located on their campus. Almost half (47.5%) of the respondents indicated that they are not happy with where they live. The findings further show that 1 187 (31.8%) of the surveyed students have transport problems. The majority of the respondents 2 827 (74.9%) would choose University of the Mega Don again if they were rechoosing a higher education institution. The survey results indicate that most surveyed students, 58.3%, rated their experience at University of the Mega Don between good and very good.